Notes on lichenicolous Pleosporales, with two new species, Didymocyrtis azorica and Pseudopyrenidium epipertusariae (Phaeosphaeriaceae) - Etayo, J.; Pino-Bodas, R. (Phytotaxa, 2021)
The identity and phylogenetic placement of some lichenicolous Pleosporales were studied using morphological and molecular data. Two new species are described, Didymocyrtis azorica on Hypotrachyna rockii, from the Azores, and Pseudopyrenidium epipertusariae on Pertusaria pertusa, from Spain in oceanic montane woods, with a Phoma-like asexual state. This is the second species of Pseudopyrenidium, and the morphological similarities with P. tartaricola are discussed. In addition, Evernia prunastri is a new host for Didymocyrtis ramalinae, and Heterodea muelleri is a new host for D. cladoniicola, which is newly reported for Australia.